Comparative Study of Seismic Hazard Analysis Using Classical PSHA and PSHA Method in Java Island, Indonesia - Goro , Garup Lambang; Irsyam, Masyhur; Meilano, Irwan; Asrurifak, M. (Geological Agency, 2024)
In general, seismic hazard analysis is conducted using a probabilistic approach (PSHA), whilst seismic risk analysis is computed using a stochastic approach. To figur out more differences between the two methods, a comparative study of those two approaches needs to be conducted. The study was conducted in Java Island which is the most populated island in Indonesia, and prone to earthquakes, particularly in the southern part due to the subduction of the Australian Plate and many active shallow faults along the island. To find out whether the hazards occurred in the risk analysis were closer to the results of Classical PSHA, it is necessary to examine the comparison of the two methods. The difference between the Event-Based and Classical methods is the use of a synthetic catalog that depends on the input value of SES (Stochastic Event Set). The research began with hazard computation with both methods, where the Event-Based PSHA method was given varying SES values. Determining the SES value in the Event-Based method is an important stage to conduct as a significant input parameter in a risk analysis, particularly the loss analysis. The comparison results conclude that the Event-Based PSHA with SES= 200,000 produced a wellconfirmed hazard map compared to the Classical PSHA result with the smallest standard deviation and variation, i.e. 0.0172 and 0.0003 respectively.